The role of the authority to control public procurement and public utility authorizations in protecting procurement contracts from corruption: a study in the light of Articles 88 and 213 of Law 15/247 related to public procurement and public utility authorizations - Hadji, Ibtissem (Journal of Human Sciences, 2022)
After the promulgation of the 1989 constitution, Algeria experienced changes in several aspects, especially in the economic aspect, which in turn affected the legal aspect, and the resulting shift in the system from a socialist to a market economy, which had the effect of establishing the legislature for many controlling authorities, especially in the financial field. In addition, the economic as the authority to control public procurement and public utility authorizations, given the effective role it plays in combating corruption, rationalizing public expenditures, and activating the role of the controlling state.